AB0099 Taxol alleviates collagen-induced arthritis in mice by inhibiting the formation of microvessels. (15th June 2017) - Xu, J; Feng, Z; Zhu, J; Chen, S; Chen, X; Li, J
Abstract : Background: Angiogenesis is one of the critical features in rheumatoid arthritis (RA). Uncontrolled neovascularization could help the infiltration of inflammatory cells and lead to synovial hyperplasia and bone destruction further. Precious studies have demonstrated that the medicine taxol (PTX) has anti-angiogenesis effects. Objectives: To evaluate the inhibitory effects of PTX on angiogenesis in a collagen-induced arthritis (CIA) mouse model. Methods: A total of 50 mice were used to induce a CIA mouse model with collagen II (CII) and complete Freund's adjuvant (CFA). Twenty-four with obvious arthritis syndrome were randomly divided into four groups: CIA model group, PTX 1.5 mg/kg group, PTX 1.0 mg/kg group, PTX 0.5 mg/kg group. In addition, 6 normal mice was regarded as the control group. PTX was administered by intraperitoneal injection in the PTX treatment groups 8 times every other day. Arthritis index scores, tissue pathology scores after HE staining and synovium microvessel density (MVD) analysis after immunohistochemical (IHC) staining were performed. Immunohistochemistry and ELISA were used to detect the expression of vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-α (HIF-1α). Additionally, the correlation between MVD and pathological scores, level of VEGF and HIF-1α in the synovium were also evaluated. Results: After PTX treatment, the three intervention group arthritis index scores (1.33±0.52, 2.00±0.63, 3.33±1.03) declined when compared with the CIA group (5.67±1.03, p<0.001, p<0.001, p=0.016). The total histological scores in the three PTX treatment groups (2.50±0.66, 3.89±0.86, 3.89±0.86) were lower than those in the CIA group (7.67±0.79, p<0.001, p<0.001, p=0.007). Similarly, PTX significantly alleviated the scores for synovitis, pannus formation and bone destruction. Compared with the CIA group (110.32±5.06/mm 2 ), the MVD of the three intervention groups decreased in dose-dependent manner (17.05±1.97/mm 2, 34.73±2.36/mm 2, 57.55±2.72/mm 2 ; p<0.001, respectively). In addition, the expression of VEGF and HIF-1α in synovial tissues and serum also decreased significantly after PTX treatment. Further analysis showed that MVD and pathological scores and levels of VEGF and HIF-1α in the synovium were positively correlated (r=0.921, r=0.944, r=0.889, r=0.969, r=0.933; p<0.001, respectively). Conclusions: PTX may alleviate CIA by suppressing angiogenesis, providing new insights into the treatment of RA. VEGF and HIF-1α may be the target for PTX suppression of microvessel formation. References: Smolen JS, Aletaha D, McInnes IB. Rheumatoid arthritis. The Lancet 2016. Park KS, Park MJ, Cho ML, et al. Type II collagen oral tolerance; mechanism and role in collagen-induced arthritis and rheumatoid arthritis. Mod Rheumatol 2009;19:581–9. Disclosure of Interest: None declared